Cu / Invar composite material and preparation method thereof
Preparation of Cu/Invar composite materials through cold spraying technology avoids element diffusion and solid solution problems caused by high temperature processing, achieves high thermal conductivity and low expansion performance, solves the problem of poor material performance in the existing technology, and provides applicable Heat sink material for high-performance electronic packaging.
Patent Information
- Application Number
- CN202411331243.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-14
AI Technical Summary
In the existing Cu/Invar composite material preparation process, the element diffusion and solid solution are caused by high temperature processing, resulting in a decrease in thermal conductivity and an increase in expansion coefficient. The material has anisotropy, making it difficult to meet the performance requirements of high thermal conductivity and low expansion.
Cold spraying technology is used to mix Cu powder and Invar alloy powder and spray and deposit it under nitrogen carrier gas to avoid long-term heating at high temperatures, ensure that the two phases are evenly distributed without diffusion, and form a Cu/Invar composite material with high thermal conductivity and low expansion, and pass Vacuum heat treatment optimizes material performance.
The high thermal conductivity and low expansion characteristics of Cu/Invar composite materials are realized, and the expansion coefficient isotropic, which improves the overall performance of the material and is suitable for high-performance electronic packaging heat sink materials.
Smart Images

Figure CN119307904A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of metal composite materials, and in particular, relates to a Cu / Invar composite material and a preparation method thereof. Background Art
[0002] Heat sink material is the most important one in electronic packaging materials or thermal management materials. Its main function is to conduct and dissipate the heat generated by semiconductor devices such as chips and transistors in time. In addition to having high thermal conductivity, it should also have a thermal expansion coefficient that matches that of semiconductors such as Si and GaAs. Otherwise, it is easy to detach and fail after being heated. In addition, it also needs to have good machinability, weldability, airtightness and other properties. Pure copper has high thermal conductivity (up to 397W / mK), but its thermal expansion coefficient is too large (up to 17×10 -6 / K), the expansion coefficient of the ceramic substrate is too different, which can easily lead to serious thermal mismatch; Invar alloy (Fe 64 Ni 36 , wt.%), also known as Invar alloy, Invar steel, invar steel, etc., has a very small thermal expansion coefficient, and the expansion coefficient near room temperature (25-30°C) is only 1-2×10 -6 / K, but its thermal conductivity is very low, only 11W / mK. Cu / Invar composite material, which is a composite of Cu and Invar alloy, is an ideal metal packaging material by making use of the high thermal conductivity of Cu and the low expansion characteristics of Invar.
[0003] The simplest composite method is to roll Cu plate and Invar alloy plate into a layered Cu / Invar / Cu (industry abbreviation CIC) composite material, whose longitudinal thermal expansion coefficient is less than 10×10 -6 / K, but the longitudinal thermal conductivity is much lower than the lateral thermal conductivity, so the heat dissipation performance is good but the thermal conductivity is poor. CIC has been commercialized as a heat dissipation material, but it is difficult to apply it to chip heat sinks with higher added value.
[0004] At present, the mainstream preparation method of Cu / Invar composite materials is mainly based on hot pressing and sintering of mixed powders. Since the solid solubility of Ni in Cu is very large, two-phase element diffusion will occur if the high-temperature treatment time is slightly longer. The thermal conductivity of the Cu phase and the expansion coefficient of the Invar phase are very sensitive to the composition. Once element diffusion occurs, the thermal conductivity of the Cu phase is significantly reduced and the expansion coefficient of the Invar phase is increased.
[0005] For example, patent CN113667852 A uses a mechanical mixture of Invar alloy powder and Cu powder in a mass ratio of 1:1, and prepares a composite material by vacuum SPS sintering. The sintering temperature is 700-800℃, the sintering pressure is 40-60MPa, and the holding time is 1-5 minutes. This process can obtain a thermal conductivity of 130.1W / mK and a thermal expansion coefficient of 12.7×10 -6 / K Cu / Invar composite material has good thermal conductivity but high expansion coefficient.
[0006] Patent CN107312945A uses a mixed powder pre-pressed at 300-600MPa and then sintered at normal pressure. The sintering is carried out under the protection of hydrogen atmosphere, and the temperature is kept at 650-800℃ for 1-3h. The Cu powder mass ratio is 30-50%, and the Invar powder is first treated with surface chemical Ag plating. The purpose is to set an interface barrier layer between the Invar powder and the Cu powder to inhibit the diffusion of elements during high-temperature sintering. The thermal expansion coefficient of the prepared composite material with a Cu content of 40% is 11.2×10 -6 / K, the thermal conductivity is 53.7W / mK, and the thermal conductivity is significantly low.
[0007] Patent CN 105803247A discloses a copper-stainless steel Invar alloy composite material and its preparation method. The stainless steel Invar alloy does not contain Ni element and is a Co-Fe-Cr alloy. The solid solubility of Cu in the three elements of Co, Fe and Cr at room temperature is very low. Through appropriate component ratio, the four elements can be melted together to form two liquid phases that are easily separated, namely, a Cu-rich liquid phase and a Co-Fe-Cr liquid phase. The patent first prepares a core / shell type self-encapsulated composite powder by vacuum induction melting-gas atomization. The powder contains two solid phases, a Cu-rich phase and a Co-Fe-Cr-rich phase, and then hot presses and sinters to obtain a bulk composite material. The optimal composition is Cu 70 Co 16 Fe 11 Cr3 (wt.%), its thermal expansion coefficient is 10.66×10 -6 / K, thermal conductivity 107.4W / mK. This comprehensive performance is good, but because the price of Co is about half that of Ni, and the powder is prepared by high-pressure argon gas atomization, the cost is high. In addition, the Cu content in the best composition is as high as 70%, but the thermal conductivity is only 27% of pure copper (the thermal conductivity of pure copper is 397W / mK). This is because a lot of other elements are still dissolved in the Cu phase, that is, the "copper-rich phase" rather than the pure copper phase, which means that it is difficult to give full play to the high thermal conductivity of copper after the high-temperature liquefaction process of smelting.
[0008] The above-mentioned technologies show that high-temperature processing such as melting and sintering easily leads to element diffusion and solid solution, which is not good for the expansion coefficient of the Invar phase and the thermal conductivity of the copper phase. Texas Instruments of the United States has developed a relatively low-temperature processing technology long ago (CuVar-a new controlled expansion, high conductivity material for electronic thermal management [J]. Electronic Components and Technology Conference, 1995:542, US Patent #5310520, 1994.), which mixes Cu powder and Invar powder and packs them in a closed copper tube under vacuum, and then extrude them at a temperature of about 600 ° C to prepare a composite material named CuVar, which has good thermal expansion performance and thermal conductivity, and the thermal expansion coefficient ranges from 6.5 to 8×10 -6 / K, thermal conductivity 100 ~ 120W / mK. However, due to the deformation of the Watt phase along the extrusion direction, the expansion coefficients in the parallel and perpendicular directions are 6.5×10 -6 / K and 8×10 -6 / K, there is obvious anisotropy, and it is easy to deform after heating. Therefore, CuVar has not gained a good market as a heat sink material. Summary of the invention
[0009] The purpose of the present application is to provide a Cu / Invar composite material and a preparation method thereof, aiming to solve the technical problem of how to prepare a Cu / Invar composite material with high thermal conductivity and low expansion.
[0010] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0011] In a first aspect, the present application provides a method for preparing a Cu / Invar composite material, comprising:
[0012] Mixing Cu powder and Invar alloy powder to obtain a mixed powder;
[0013] The mixed powder is sprayed and deposited on a substrate by cold spraying technology to form a Cu / Invar composite material. The spraying temperature is 600-800° C. and the carrier gas is nitrogen.
[0014] In a second aspect, the present application provides a Cu / Invar composite material, which is prepared by the preparation method provided in the first aspect of the present application. The Cu / Invar composite material thus formed has two phases evenly distributed without element diffusion, so that the Cu / Invar composite material has the characteristics of high thermal conductivity and low expansion, and the expansion coefficient is isotropic. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a metallographic structure diagram of the Cu / Invar composite material prepared in the example of the present application. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0017] At present, the preparation process of Cu / Invar composite materials has either serious diffusion between elements or serious anisotropy, which makes its comprehensive performance unsatisfactory. Cold spray (CS: Cold Spray) technology is a coating preparation method based on high-speed particle solid deposition. It uses high-pressure gas as an accelerating medium. The spray powder particles are heated and then accelerated by a gas with a certain temperature and pressure. After being ejected from the Laval nozzle of the spray gun, they impact on the substrate at high speed to produce a certain plastic deformation, thereby depositing on the surface of the substrate to form a coating. The subsequent ejected particles continue to deposit on the coating and gradually form a bulk material. In principle, a bulk material of unlimited thickness can be formed. Therefore, it is also an additive manufacturing or 3D printing process, which is characterized by almost no oxidation and a fast deposition speed, which can achieve a deposition speed of kilograms per minute.
[0018] Cold spraying technology requires that the powder used must have good plasticity to ensure molding efficiency, and both Cu and Invar alloys have face-centered cubic structures and good plasticity. In addition, cold spraying is not room temperature spraying, and the powder needs to be heated to increase its plastic deformation ability. It is just that the preheated inert gas (nitrogen or helium) is used as the carrier gas and powder heating medium to achieve heating within a very short flight distance. The heating time is very short, only milliseconds, and the heating temperature is lower than the melting point of the powder. Compared with the heating media such as fuel flames, arcs, and plasma flames used in thermal spraying, the high-temperature and high-pressure gas of cold spraying begins to cool down after being ejected from the nozzle, and the thermal effect on the deposited substrate is very low. Therefore, the substrate temperature is generally not higher than 200°C, making it difficult for the deposited material to undergo phase change or diffusion. Similarly, compared with long-term high-temperature heating processes such as smelting and sintering, the heating temperature of the cold spraying process is low and the time is short. The Cu atoms do not have enough energy and time to diffuse into the Invar phase. Similarly, the Fe atoms and Ni atoms do not have enough energy and time to diffuse into the Cu phase, thus avoiding solid solution or diffusion and giving full play to the performance characteristics of the two phases.
[0019] Based on this, in the embodiment of the present application, Cu powder and Invar alloy powder are mixed, and a cold spraying process is used to prepare a Cu / Invar composite block material with uniform two-phase distribution, high density and no element diffusion. The specific solution is as follows.
[0020] In a first aspect, an embodiment of the present application provides a method for preparing a Cu / Invar composite material, comprising the following steps: mixing Cu powder and Invar alloy powder and spraying the mixture onto a substrate using a cold spraying process to deposit the Cu / Invar composite material, wherein the spraying temperature is 600-800° C. and the carrier gas is nitrogen.
[0021] In some embodiments, the particle size of the Cu powder is 15-53 μm. The particle size of the Invar alloy powder is 15-53 μm.
[0022] In some embodiments, the mass ratio of Cu powder to Invar alloy powder is 20:80 to 70:30; specifically, the Cu / Invar composite material can be obtained by cold spraying according to the above ratio. x (Fe 64 Ni 36 ) 100-x , x = 20-70, overall, Cu 50 (Fe 64 Ni 36 ) 50 The comprehensive effect is better. The Cu powder and Invar alloy powder can be spherical Cu powder and Invar alloy powder prepared by atomization method.
[0023] In some embodiments, the substrate selected for the cold spraying process includes an aluminum substrate. Before spraying the mixed powder on the substrate surface, the substrate is first subjected to ultrasonic cleaning. After cleaning, the mixed powder can be better deposited on the substrate surface. Exemplarily, the substrate surface can be subjected to pretreatment steps of grinding, surface degreasing, ultrasonic cleaning, and drying.
[0024] In some embodiments, the mixed powder is cold sprayed with nitrogen as a carrier gas and deposited on the surface of the substrate under the following conditions: (1) the mixed powder is sprayed vertically toward the substrate surface; (2) the vertical distance between the nozzle and the substrate surface when the mixed powder is sprayed is 10 to 30 mm; (3) the nozzle movement speed when the mixed powder is sprayed is 180 to 220 mm / s; (4) nitrogen is used as a carrier gas when the mixed powder is sprayed, the gas pressure is 3 to 5 MPa, and the temperature is 600 to 800°C.
[0025] For example, when spraying, a tungsten carbide spray gun is used. When the mixed powder is sprayed, the nozzle of the spray gun is perpendicular to the substrate surface, so that the deposition efficiency is the highest. When the mixed powder is sprayed, the vertical distance between the nozzle and the substrate surface is 10 to 30 mm, so that the mixed powder sprayed from the nozzle can quickly hit the substrate surface and deposit quickly in less than 1 ms. When the mixed powder is sprayed, the nozzle moves along the substrate surface at a speed of 180 to 220 mm / s, so that the Cu / Invar composite block material of the required size is formed on the substrate surface.
[0026] In some embodiments, the preparation method further includes: cutting and separating the Cu / Invar composite material from the surface of the substrate, and then performing vacuum heat treatment. The hardness of the composite material is appropriately reduced by vacuum heat treatment to facilitate subsequent machining. For example, the substrate and the Cu / Invar composite material are cut and separated by spark wire cutting. The cut Cu / Invar composite material is ultrasonically cleaned and blown dry with acetone to remove oil impurities on its surface, and then vacuum heat treated. Among them, the conditions for vacuum heat treatment include: 500-600°C for 1-3h.
[0027] The mixed powder is deposited on the substrate by cold spraying to obtain a Cu / Invar composite material with a density of more than 97%. The hardness of the copper phase in the sprayed state can be 94.97-126.83 Hv, and the hardness of the Invar phase can be 188.7-254.5 Hv. The thermal conductivity range can be 21-115 W / m·k, and the expansion coefficient can be 3-13×10 -6 / K range changes. Further through the above-mentioned cutting separation and vacuum heat treatment, the hardness is reduced, while the thermal conductivity can be further increased, and the expansion coefficient only increases slightly. Overall, the comprehensive effect of subsequent vacuum heat treatment is better.
[0028] In the second aspect, the embodiment of the present application provides a Cu / Invar composite material, which is prepared by the above-mentioned preparation method. For example, copper powder and Invar alloy powder are used as raw materials, and then deposited on a substrate by cold spraying to obtain a Cu / Invar composite material with a thickness of at least 6 to 10 mm and a density of more than 97%. After subsequent cutting and further vacuum heat treatment, the hardness is significantly reduced, and the comprehensive performance is further improved, which is expected to be used as a high-performance electronic packaging heat sink material.
[0029] The following describes the invention in conjunction with specific embodiments.
[0030] Example
[0031] The preparation method of the Cu / Invar composite material comprises the following steps:
[0032] (1) Material preparation
[0033] The high-purity near-spherical Cu powder and Invar alloy powder (Fe 64 Ni 36 ), and mechanically mixed evenly in the ratio of Cu:Invar of 20:80, 30:70, 40:60, 50:60, 60:40 and 70:30 respectively.
[0034] (2) Spraying process
[0035] Substrate pretreatment: A pure aluminum plate with a size of 200 mm×100 mm×10 mm (length×width×thickness) was ground and polished, ultrasonically cleaned in an acetone solution, and the surface impurities were blown off.
[0036] Cold spraying process: vertically spray the mixed powder on the surface of the pretreated aluminum substrate to prepare the Cu / Invar composite material with a coating thickness of 10 mm. Then the aluminum plate and the Cu / Invar composite material are cut and separated, ultrasonically cleaned and blown dry with acetone to remove the oil and impurities on the surface to obtain the Cu / Invar composite material. The working gas and powder feeding gas for spraying are both high-purity nitrogen (99.9999 vol%), the spraying pressure is 5 MPa, the working gas temperature is 700 ° C, the vertical distance between the nozzle and the surface of the aluminum substrate during spraying is 20 mm, and the nozzle moving speed is 200 mm / s.
[0037] Performance Testing
[0038] The metallographic structure observation diagram of the Cu / Invar composite material of the embodiment is as follows Figure 1 As shown, it can be seen that Cu and Invar are evenly distributed. The room temperature thermal conductivity and the average thermal expansion coefficient between 20-100°C are shown in Table 1; among them, the sprayed state refers to the Cu / Invar composite material sample obtained after spraying, and the heat-treated state refers to the sample after the sprayed material has been vacuum heat-treated at 500°C-3 hours. The expansion coefficients of the sprayed samples were measured in the thickness direction (along the spraying direction) and the horizontal direction (perpendicular to the spraying direction). There is no obvious difference in the expansion coefficients in the two directions, which can be considered as isotropic materials. Therefore, the heat-treated samples only need to measure the expansion coefficient in the horizontal direction.
[0039] Table 1
[0040]
[0041] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a Cu / Invar composite material, characterized in that: include: Mixing Cu powder and Invar alloy powder to obtain a mixed powder; The mixed powder is deposited on a substrate by a cold spraying process to form a Cu / Invar composite material, the spraying temperature is 600-800° C., and the carrier gas is nitrogen.
2. The preparation method according to claim 1, characterized in that The mass ratio of the Cu powder to the Invar alloy powder is 20:80 to 70:30; and / or, The particle sizes of the Cu powder and the Invar alloy powder are independently 15 to 53 μm.
3. The preparation method according to claim 1, characterized in that: The mixed powder is sprayed vertically toward the surface of the substrate; and / or, The vertical distance between the nozzle and the substrate surface when the mixed powder is sprayed is 10 to 30 mm.
4. The preparation method according to claim 1, characterized in that: The nozzle movement speed when the mixed powder is sprayed is 180-220 mm / s; and / or, Nitrogen spraying is used with a gas pressure of 3 to 5 MPa.
5. The preparation method according to claim 1, characterized in that: The preparation method further comprises: The Cu / Invar composite material is cut and separated from the surface of the substrate, and then subjected to vacuum heat treatment.
6. The preparation method according to claim 5, characterized in that: The vacuum heat treatment conditions include: 500-600° C. for 1-3 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The Cu / Invar composite material has a thickness of at least 6 to 10 mm.
8. The preparation method according to any one of claims 1 to 6, characterized in that: The substrate includes an aluminum substrate.
9. The preparation method according to any one of claims 1 to 6, characterized in that: Before spraying the mixed powder onto the surface of the substrate, the substrate is firstly subjected to ultrasonic cleaning treatment.
10. A Cu / Invar composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Low-expansion high-thermal-conducting copper-stainless invar alloy composite material and preparation method thereof
CN105803247A
Preparation method of Cu / Ag (Invar) composite material for electronic packaging
CN107312945A
Powder metallurgy preparation method of high-thermal-conductivity Cu-Invar bimetal-based composite material
CN113667852A